Meningkatkan Minat dan Hasil Belajar Siswa Melalui Media E-Book Berekstensi Epub Di MTs. Al-Amin Silo - Mamluatul Hasanah; Haning Hasbiyati; Umi Nurjanah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
Based on the results of observations in the 8th Class of MTs. Al-Amin in science learning shows that teachers always use textbook as the main learning media. The selection of unvaried media makes the students’ interest in learning science low causes the low learning outcomes, as evidenced by the data about 80% shows that the value of students was ≤70 still below the minimum completeness criteria. This study aims to improve students’ learning outcomes and interests through EPUB extension of E-Book media. The type of research used is classroom action research (CAR). Based on the results of the study, students’ learning outcomes in the first cycle was 69 and it had increased to 76 in the second cycle. Students' interest was obtained by 61% in the first cycle and there was an increase to 79% in the second cycle. Thus, it can be concluded that there is an improvement in students’ interest and learning outcomes in the application of E-book media with EPUB extensions to the material of Motion and Living Beings. Keywords : learning outcomes, e-book, EPUB.